STEM TECHNOLOGY IN THE STUDY OF EDUCATIONAL ROBOTICS - Ivanovich Gdansky, Nikolay; Lvovna Kulikova, Natalia; Alekseevich Budnik, Alexander; Vladimirovich Sokolov, Igor (Revista Inclusiones, 2019)
STEM education is aimed at the formation of adaptation skills to those changes that occur in technology and science and will become key for further education and employment. One of the directions for the introduction of educational STEM technologies is educational robotics. In recent years, advances in robotics and automated systems have changed personal and business areas of life. Modern production and industry need specialists with knowledge of robotics. Therefore, the introduction in the educational program of the section related to robotics is gaining increasing importance and relevance now. The objectives of the study are to justify the relevance and importance of introducing educational robotics in schools, determine the state of teaching robotics and outline ways of introducing educational robotics and ways of preparing future robotics teachers. In the study, the current state and tasks of educational robotics in the secondary education system, as well as an approach to the study of robotics using STEM education, are discussed at the theoretical level. Based on an expert survey, the main characteristics of STEM education and the tasks of introducing educational robotics in STEM education are determined and a characteristic of the state of teaching robotics in schools is given.